Reconsidering a philosophy for Nigerian education (2014)
This paper examined the Nigerian philosophy of education as stated in the 2004 National Policy on Education. It argues from the position that philosophy of education ought to consist of the nature of human beings and of the society, what the society considers the best type of knowledge worth having and the value system considered most valuable. The paper speculates that communalistic living and effective citizenship are essential elements that should be reconsidered in the Nigerian Philosophy of Education